Effective Team Communication Stimulates Teacher Effectiveness: A Study of a Private College in Attock City, Pakistan - SHEHZAD, NAUREEN (2018)
Communication is an art, a skill that brings people close to each other and builds a bond of trust and dependence upon each other. Researchers since the early nineteenth century have defined and explored communication in different scenarios and have devised ways to improve and refine it. Communication in educational institutions holds much importance since a teacher collaborates, communicates and delegates responsibilities and communicates at various levels in the institution. Communication among teachers plays a pivotal role in teacher’s effectiveness and all-inclusive academic success of the students. The aim of this study is to determine the effectiveness of communication that exists between teachers and leaders and its effects on teacher’s proficiency. With current researches showing a link between teacher effectiveness and student achievement, it is important to consider how team teacher’s communication impact teacher’s effectiveness. The prominent theories and models of communication that give primary importance to communication are Kotter’s Model for Change, Shannon and Weaver’s transactional model of communication, which is a building block in today’s modern communication. Communication primarily depends on interpersonal skills that are expressed in the Johari Window while Leader-member Exchange theory discusses the importance of shared and distributed leadership which is suitable in today’s era. The research questions are answered through a mixed methodology approach including both qualitative and quantitative methods of data collection. The survey questionnaire is designed in Qualtrics that includes Likert scale closed-ended questions for quantitative data collection and open-ended questions for qualitative data collection. On this basis, it is revealed that age, gender and years of experience do not affect team communication and teaching efficacy. Qualitative data shows that teachers in this school perceive a high-quality communicative relationship with team leaders, a collegial environment that enhances teacher effectiveness and a faith in leadership style existing in the college. The research can be expanded to the whole school and it can include how team communication effects a student’s achievement. The research can be generalized to the other educational institutions or other campuses in different parts of the country, which would reveal rich variety of qualitative and quantitative data.